Article review of "financial management and accounting in state Islamic religious councils in Malaysia: a grounded theory" by Abdul Rahim Abdul Rahman and Andrew Goddard / Wan Noor Hazlina Wan Jusoh - Wan Jusoh, Wan Noor Hazlina (2013)
Financial management and accounting are pivotal in any organization since the success or failure of the organization depends on how the assets are managed within the organization (Accounting Schools Online, 2012) regardless of its nature whether it is a business or religious entity. However, as argued by the researchers in this sociology research, the study on cultural and social background is needed in order to understand the organization's management. This is in line with what has been found by Hofstede (1998) that organizations have cultures, even parts of organizations may possibly have different subcultures.